Angka Paling Mungkin (Most Probable Number/MPN) Coliform Sampel Kue Bingke Berendam di Pontianak - Elvi Rusmiyanto P.W, Dini Agustin, Rahmawati, (Universitas Tanjungpura, 2019)
Bingke berendam cake is one of the traditional foods of Pontianak which is made from rice flour, eggs, sugar and coconut milk. Materials that are used such as sugar, milk and eggs are ingredients that are easily damaged and polluted by microbes. This study aimed to to find out the Most Probable Number (MPN) of coliform bacteria in bingke cakes. Taking bingke cake samples was done at five bingke cake shops in Pontianak city. Isolation of Coliform bacteria used the MPN method, with two stages, namely the estimator test tand the assertive test. Based on the results of this study, the five samples had MPN values ranging from 23 MPN/g to> 100 MPN/g. All samples had MPN values that exceed the threshold so that they did not meet the requirements for PERKA BPOM No. 16 of 2016, which is a 11 MPN/g.